Use of service robots in hospitality: An observational study in terms of technology acceptance model - Çalişkan, Gürkan; Sevim, Burhan (SAGE Publications, 2023)
This study aims to explore hospitality customers’ behavioral intentions and reactions toward service robots from the perspective of the Technology Acceptance Model. Kastamonu University Scientific Research Projects Coordination Department has supported this research. In this context, the service robot was leased. The service robot has been shown to customers in the lobbies, restaurants, rest areas, and cafes of accommodation establishments. Customers were enabled to interact with the robot. The participant observation method was adopted in the study. Unstructured interviews were conducted. The data divided into categories from the perspective of the Technology Acceptance Model were processed using the MAXQDA analysis tool. The density map was drawn from the “Document Portfolio.” The data were obtained as a result of participant observation. It is divided into two categories. These; are “Behavioral Responses” and “Cognitive and Emotional Responses.” The most prominent themes within the categories are video/photo taking, speaking, touching (behavioral), excitement, liking, and having fun (cognitive and emotional). The user rate of these reactions is 7/10 on average. It was observed that the participants enjoyed, were satisfied, and wanted to interact with the service robot. These findings reveal that behavioral intentions related to technology acceptance may occur against service robots.
Keywords: 16. Peace & justice; 3. Good health